Archaeology, politics and nationalism in nineteenth- and early twentieth-century Ethiopia: the use of archaeology to consolidate monarchical power. Issue 3 (3rd July 2018) - Zena, Ashenafi Girma
ABSTRACT: Ethiopia's Christian and medieval past was perceived and exploited by Menilek II, the founder of modern Ethiopia, to consolidate his own political power and resist the encroachments of European states in the late nineteenth and early twentieth centuries. This paper shows how Menilek used archaeological data to assert his continuity with the Solomonic dynasty and consolidate his political authority in order to strengthen historically documented narratives about his genealogical ties with ancestors who had established and ruled one of the great ancient African civilisations at Aksum. It also shows how Menilek supervised and ordered excavations to search for traces of Ethiopia's Christian past in the ruins of medieval royal churches and former royal camp sites, while emphasising his pivotal role in inviting the first foreign scholars to conduct archaeological excavations at historical sites in the country. It argues that this combination of archaeological activities was instrumental in developing a sense of Ethiopian national identity during Menilek's reign and thereafter.